PEMBERDAYAAN UMKM MELALUI PROGRAM KAMPUNG BEBAS RENTENIR (KBR) KUBE BERDAYA OLEH RUMAH PEMBERDAYAAN MASYARAKAT (RPM) DI PAMULANG, KOTA TANGERANG SELATAN - Hana Fairuz; WG. Pramita Ratnasari (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
Abstract Small and Medium Enterprises (SME) are a type of business that is still growing rapidly in Indonesia. There are still many SME actors who have weak economic values, this is due to low business capital ownership so that business actors tend to seek loans with easy and quick access conditions. Loans through moneylenders are considered to be able to help the economic activities of business actors, on the other hand moneylenders have some bad impacts that can harm the borrower because they provide early discounts and interest. This study aims to determine the process and results of empowerment in the Moneylender Kampung Bebas Rentenir. This study uses a qualitative approach. Informants were selected using a purposive sampling technique. Data was collected using observation, interviews, and documentation studies. The data was analyzed using the data analysis technique proposed by Miles and Huberman, and Triangulation was used as data validity technique. The results of the research that have been obtained show that in the implementation of empowering SME in the program Kampung Bebas Rentenir, there is an empowerment process including awareness process, knowledge transformation, and intellectual ability improvement. The results of the empowerment of SME carried. The results of the empowerment of SME carried by Rumah Pemberdayaan Masyarakat in program Kampung Bebas Rentenir is to have the ability to fulfill basic needs, to increase income, and to participate in development.